2019
DOI: 10.7759/cureus.5818
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Outcomes after Non-traumatic Intracerebral Hemorrhage

Abstract: Background Nontraumatic intracranial hemorrhages (ICH) are serious cerebrovascular events with high morbidity and mortality. They occur in about two million people a year worldwide. While ICH continues to be a focus of research in the medical community, there is little data on the differences in outcomes by gender. We aimed to further investigate these differences in our study. Methods This analysis involves a de-identified dataset of all adult patients who presented to one of our hospital system's emergency d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…Concerning mortality, we did not observe that women fared worse than men did, probably because our study population differed from those in previous studies, with women not being older than men, suggesting that a combination of both sex and age may contribute to differences in outcome after ICH [10,20]. Concerning functional outcome at hospital discharge after the ICH, however, female patients achieved a favorable outcome (mRS score 0-3) more often than male patients did, despite less aggressive treatment.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Concerning mortality, we did not observe that women fared worse than men did, probably because our study population differed from those in previous studies, with women not being older than men, suggesting that a combination of both sex and age may contribute to differences in outcome after ICH [10,20]. Concerning functional outcome at hospital discharge after the ICH, however, female patients achieved a favorable outcome (mRS score 0-3) more often than male patients did, despite less aggressive treatment.…”
Section: Discussioncontrasting
confidence: 68%
“…Incidence of ventriculostomy-related infection was the same in both sexes, ruling out that this relevant EVD-related morbidity is causing poorer functional outcome in men. Previous findings concerning sex-related differences in mortality after ICH are conflicting: studies have reported that younger women (< 65 years old) with ICH had a lower mortality than men but also that women suffered from higher mortality and morbidity after ICH [19] [20]. In secondary ICH related to vascular abnormality, female sex was an independent risk factor for poor outcomes [21].…”
Section: Discussionmentioning
confidence: 99%
“…With regards to sex, there is still conflicting literature about outcomes and mortality [ 8 ]. Several studies point to higher morbidity and mortality in women with ICH secondary to the presence of intraventricular hemorrhage [ 9 , 10 ]. However, a 2020 European study analyzing the results of the INTERACT 1 and 2 trial noted that possible under-representation of women and data being based on single-center studies may account for uncertainty in outcomes between men and women [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sex differences in outcomes have not been fully characterized in the pathophysiology of ICH. For younger patients, female sex was protective, but at age >60 years, female sex was a risk factor for death or discharge to hospice ( Umeano et al, 2013 ; Craen et al, 2019 ). The mortality rate of ICH increased from 20% in female patients under 75 to 26% in those over 75 ( Zia et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%